2021
DOI: 10.21203/rs.3.rs-659290/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acceptability and Safety of Thermal Ablation to Prevent Cervical Cancer in Sub-Saharan Africa

Abstract: Background - The World Health Organization recommends thermal ablation as an alternative to cryotherapy to treat women with precancerous lesions in low-resource settings. However, limited data are available on women’s experience and adverse events (AEs) of the procedure in the context of Sub-Saharan Africa. The objective of this study was to evaluate the acceptability and safety of thermal ablation in women screened positive for precancerous cervical lesions.Methods - Asymptomatic women aged 30-49 years old li… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In the few studies available, the use of thermal ablation for the treatment of cervical lesions is generally feasible and acceptable, [14][15][16] yet there is some heterogeneity in the literature in the acceptability of thermal ablation across diverse settings. 15 Some recent studies have found initial evidence of minimal side effects of thermal ablation immediately after treatment, 17,18 but gaps remain in knowledge about the side effects and potential adverse events that occur throughout the recovery period of up to 6 to 8 weeks after treatment, and detailed data on the acceptability of the treatment and subsequent side effects are needed. With a global shift to HPV-based screening, appropriate management algorithms need to be implemented to minimize treatment related harms, 19 20,21 and pertinent details for this study are presented below.…”
Section: Introductionmentioning
confidence: 99%
“…In the few studies available, the use of thermal ablation for the treatment of cervical lesions is generally feasible and acceptable, [14][15][16] yet there is some heterogeneity in the literature in the acceptability of thermal ablation across diverse settings. 15 Some recent studies have found initial evidence of minimal side effects of thermal ablation immediately after treatment, 17,18 but gaps remain in knowledge about the side effects and potential adverse events that occur throughout the recovery period of up to 6 to 8 weeks after treatment, and detailed data on the acceptability of the treatment and subsequent side effects are needed. With a global shift to HPV-based screening, appropriate management algorithms need to be implemented to minimize treatment related harms, 19 20,21 and pertinent details for this study are presented below.…”
Section: Introductionmentioning
confidence: 99%